2009
DOI: 10.1016/j.pec.2009.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Goal setting in diabetes self-management: Taking the baby steps to success

Abstract: Objective To evaluate the usefulness of a diabetes self-management guide and a brief counseling intervention in helping patients set and achieve their behavioral goals. Methods We conducted a quasi-experimental study using a one group pretest posttest design to assess the effectiveness of a goal setting intervention along with a self-management guide. English- and Spanish-speaking patients with diabetes had one in-person session and two telephone follow-up calls with a non-clinical provider over a 12–16-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
115
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 19 publications
5
115
0
2
Order By: Relevance
“…Previous study similarly reported that individual education sessions combined with an explanatory booklet were effective in improving the patients' diabetic foot care knowledge and behaviors within a period of 6 months (Vatankhah et al, 2009). Furthermore, the use of counseling related action plans and discussion of the subjects' difficulties in performing DFCB was instrumental in strengthening their problem solving skills, allowing them to overcome barriers in achieving the behaviors they wanted to implement (DeWalt et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous study similarly reported that individual education sessions combined with an explanatory booklet were effective in improving the patients' diabetic foot care knowledge and behaviors within a period of 6 months (Vatankhah et al, 2009). Furthermore, the use of counseling related action plans and discussion of the subjects' difficulties in performing DFCB was instrumental in strengthening their problem solving skills, allowing them to overcome barriers in achieving the behaviors they wanted to implement (DeWalt et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…These goals and action plans also provided clear guidance for the subjects as to what activities needed to be undertaken and how the desired goals were to be achieved. Additionally, the manner in which the goals were set allowed the subjects to set the most achievable goal first and once that goal was achieved that served to strengthen the subject's self-confidence, which in turn provided encouragement for them to successfully achieve further goals (Bodenheimer and Handley, 2009;DeWalt et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…health can benefit [3]. Examples of translational behavioral interventions that span these blocks have been presented elsewhere, such as the application of basic scientific understanding of diabetes and its management (T1) to develop behavioral interventions for diabetes self-management (T2) [4] and the cultural tailoring of these same interventions to most effectively reach identified populations in need (T3) [5].…”
mentioning
confidence: 99%